OPTIMALISASI PERAN KECAMATAN DALAM PENGELOLAAN KEUANGAN DESA - Zuhrizal Fadhly (Jurnal Public Policy, 2017)
This research is about Optimalization of District Role in Village Financial Management. The purpose of this study is to optimize the role of sub-districts in village financial management. This study uses normative legal research methods (legal research), ie. studies that refer to the principles, norms contained in laws and regulations, ranging from Laws, Government Regulations, Ministerial Regulations, Regional Regulations/Qanun, Governor Regulations and Regents Regulations relating to the duties of sub-districts in the guidance and supervision village finance. The approach used in this study is the state approach, and the concept approach, by examining the research material consisting of primary, secondary and tertiary legal materials. The research material is analyzed by qualitative approach, with the aim to understand the meaning of the legal material that has been collected, which then interpreted normatively, logically and systematically by using inductive method. The results of this study indicate that the function of guidance and supervision that has been carried by the sub-district does not clearly reveal the intent and how the business process runs. The definition of village financial management is evident in 5 aspects: planning, implementation, administration, reporting, and accountability need to be clarified by stating the extent of the role of the kecamatan in each stage. In the planning aspect, the sub-districts need to be involved intensively when the village government processes the village development planning. This is aimed at ensuring that the development planning prepared by the village government is in line with regional development planning. District / city governments need to facilitate kecamatan to increase their role in supervising village financial management. One thing that can be done is to facilitate kecamatan devices to obtain education, training, in the framework of competence development. Provincial governments can play a role in financing aspects to strengthen the capacity of kecamatan equipment through education and training.